Konstelasi Kekuasaan dalam Jaringan Parkir Informal di Kota Makassar: Integrasi Rhizomatic Network Analysis dan Assemblage - Andi Erin Triharta; Kerenhapukh Larassati Samma; Defri Defri (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2026)
Informal parking remains a persistent urban phenomenon in Makassar City, especially in areas with high economic activity and mobility. It is often seen merely as a regulatory violation, although it reflects complex social dynamics and power relations. This study analyzes the configuration of informal parking networks and how formal and informal relations shape the control of parking space. Using a qualitative approach through observation and in-depth interviews with parking attendants, PD Parking Makkassar, and local officials, the study applies Rhizomatic Network Analysis and assemblage. The findings show that informal parking operates through dispersed, adaptive, and non-hierarchical networks involving multiple actors, including non-formal actors who influence protection and economic flows. Legal status often emerges after practices are established, blurring formal and informal boundaries. Informal parking is thus best understood as a spectrum of practices shaped by dynamic power relations and urban spatial configurations.